Impacts of land use conversions on soil organic carbon in a warming-induced agricultural frontier in Northern Ontario, Canada under historical and future climate. (10th June 2023) - Jiang, Rong; Jayasundara, Susantha; Grant, Brian B.; Smith, Ward N.; Qian, Budong; Gillespie, Adam; Wagner-Riddle, Claudia
Abstract: Land conversion from forest to agriculture in higher latitude regions such as the Great Clay Belt of northern Ontario, Canada is expected to intensify due to warming. It is critical to minimize soil organic carbon (SOC) loss, but there is limited understanding of best land management practices for these Northern agricultural frontiers. We conducted a measurement campaign to assess changes in SOC after land conversion from native forest to either permanent pasture or to arable cropping by measuring SOC content (0–60 cm) at six farms with different land uses over the past 68 years (1950–2018). The Denitrification-Decomposition (DNDC) model was validated for historical SOC trends and then used to assess the impacts of future climate change on crop yields, SOC stocks, and SOC sequestration rates from 1954 to 2070 under three Shared Socio-economic Pathways (SSPs) scenarios from the Coupled Model Intercomparison Project Phase 6. Three land uses (1) continuous barley-oats (BO), (2) continuous Legume hay-BO, (3) continuous Pasture; and two land use conversions (4) pasture from 1954 to 2014 and then converted to BO from 2015 to 2070 (Pasture » BO) and (5) BO from 1954 to 2014 and then converted to pasture from 2015 to 2070 (BO » Pasture) were considered. Averaged across all six farms, the measured SOC stocks 68 years after conversion from forest were 22.7 and 25.3% higher under pasture than under forest and arable cropping, respectively. The DNDC demonstrated good performance in simulating yields of annual crops, legume hay and pasture as well as SOC stocks across all sites. Under future climate scenarios, higher SOC stocks were predicted for all land use conversions relative to the historical period, except for Pasture » BO. Under different land use, predicted SOC stocks were highest for continuous pasture, followed by BO » Pasture, Pasture » BO, Legume hay-BO and lowest for continuous BO. The DNDC predicted that the SOC sequestration rate would decrease for all land uses in the period 2015–2070 relative to 1954–2014, except for BO » Pasture. The predicted change declined from 0.35 to 0.22–0.28 Mg C ha −1 yr −1 for continuous pasture, but when change in management occurred from BO to pasture the rate of SOC gain increased. This underscores the potential role of pasture and crop diversification in avoiding SOC losses in agricultural frontiers induced by climate-warming. Highlights: SOC stocks under pasture were higher than arable land after forest conversion. DNDC well simulated crop yields and SOC under cereal, forage, and pasture systems. Future SOC stocks were estimated to increase in the Clay Belt of northern Ontario. Highest SOC stocks would occur under continuous pasture under future climate scenarios. SOC sequestration rates (2015–2070) decreased for most scenarios relative to the historical period (1954–2014).